Resistance Training Combined With Cognitive Training Increases Brain Derived Neurotrophic Factor and Improves Cognitive Function in Healthy Older Adults - Castaño, Luz Albany Arcila; Castillo de Lima, Vivian; Barbieri, João Francisco; Lucena, Erick Guilherme Peixoto de; Gáspari, Arthur Fernandes; Arai, Hidenori; Teixeira, Camila Vieira Ligo; Coelho-Júnior, Hélio José; Uchida, Marco Carlos (Frontiers in Psychology, 2022)
Background: The present study compared the effects of a traditional resistance training (TRT) and resistance training combined with cognitive task (RT+CT) on body composition, physical performance, cognitive function, and plasma brain-derived neurotrophic factor (BNDF) levels in older adults. Methods: Thirty community-dwelling older adults were randomized into TRT and RT+CT. Exercise groups performed a similar resistance training (RT) program, twice a week over 16 weeks. Cognitive Training involved performing verbal fluency simultaneously with RT. Exercise sessions (eight resistance exercises) were performed 2-3 sets, 8-15 repetitions at 60-70% of 1-repetition maximum (1RM). Body composition, physical function, cognitive performance, and BDNF levels were assessed before and after intervention period. Results: The physical performance was similarly improved in response to both TRT and RT+CT (p=0.001). However, exclusive improvements on cognitive function (p<0.001) and BDNF levels (p=0.001) were observed only after RT+CT. Conclusion: The RT program associated with a cognitive task, improved physical and cognitive performance in healthy older adults.